The Influence Of Population, Open Unemployment Rates and IPM On Income Inequality In Lampung Province - Megantoro, Ardi; Hanafi, Syafiq Mahmadah; Ritonga, Anas Habibi; Wijaya, Muhammad Rudi (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
One of the problems in the regional growth and development process is the disparity in income distribution, which can then result in income gaps. This research aims to analyze the influence of population, open unemployment rate and IPM  on income inequality in Lampung Province for the 2017-2020 period. Using data consisting of 15 districts/cities in Lampung Province in the 2017-2020 period. Hypothesis testing uses coefficient of determination, simultaneous and partial tests. The research results show that the variables of population size and open unemployment rate have no effect on income inequality, while the IPM  variable has an effect on income inequality.